Analisis Hukum Penghapusan Merek Ikea - Nur Febry Rahmadhiani; Catharina Ria Budiningsih Ria Budiningsih (Fakultas Hukum, Universitas Islam Bandung, 2017)
Trademarks have important functions for their owners, especially in the global trading era. Trademarks give indication of the origin and the quality of the traded goods or services. Trademark owners have the exclusive rights to authorize or prohibit others from using the same or similar marks with their own. Indonesia using a constitutive registration system, namely an exclusive right is granted for a registered trademark. A trademark applicant may not register the same mark with another person's well-known trademarks. A registered trademark must be used. Annulment of a trademark is done when the mark is not used for three consecutive years. Supreme Court Decision No.264 K/Pdt.Sus-HKI/2015 which held that IKEA owned by Inter IKEA System was annulled and the registration of ikea owned by PT Ratania Khatulistiwa was valid. The result of normative analysis on the case showed that the annulment of Inter IKEA System trademark and the validity of trademark application by PT Ratania Khatulistiwa did not automatically recognize the ownership of Ikea by PT Ratania Khatulistiwa. Judge verdict resulted Inter IKEA System’s right to be excluded from trademark registration system so as allowing anyone to register the Ikea trademark. PT Ratania Khatulistiwa has exclusive rights if the application has passed the registration procedure and has a trademark certificate. If Inter IKEA System wishes to defend the same trademark, it must file an objection to the Directorate General of Intellectual Property and file a cancellation of the new trademark owner in court. If it has not succeeded it can still appeal and re-register. In general, trademark annulment occurs when a trademark is not used in the trade in goods and services. If the old owner still wants the same trademark rights, it must apply for a trademark registration and follow the entire registration procedure. If another party has first filed a trademark application, the former owner may file an objection. If this attempt fails, he may file a cancellation to the Commercial Court, the cassation, and a court review. It is recommended that the registered trademark owners use their registered trademarks. Long roads must be taken if the trademark rights is removed because it is not in use but the owner still wants the trademark rights.